Optical Solitons for Complex Ginzburg-Landau Model with Beta Derivative in Nonlinear Optics - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Amer Scientific Publishers, 2018)
In this paper, we present some new optical solitons for Complex Ginzburg-Landau equation (CGLE) involving Kerr Law in nonlinear optics. Two integration schemes which are extended Jacobi elliptic function (EJEF) and generalized projective ricatti (GPR) methods are applied to reach such solutions. The governing equation in the present paper involves beta derivative. The constraints conditions for the existence of soliton solutions are reported. Numerical simulations of some of the obtained solutions are illustrated.
Keywords: CGLE; Beta Derivative and EJEF; GPR Methods